2012
DOI: 10.1111/j.1365-2648.2011.05929.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing advanced cancer pain in older adults with dementia at the end‐of‐life

Abstract: Aim To assess advanced cancer pain in older adults with dementia at the end-of-life. Background Self-report is the gold standard for pain assessment; however, people with Alzheimer’s disease may lose the ability to report pain. Biochemical and neuropathological changes occur in Alzheimer’s disease that impairs the affective, sensory, and motor pain processing regions of the brain. Because people with severe Alzheimer’s disease may lose the ability to report their sensory and emotional response to pain verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 30 publications
1
71
0
1
Order By: Relevance
“…McDonagh et al (2016) suggested that age-related changes in the processing and interpretation of pain may imped the sensation of pain among older adults, thereby reducing their ability to self-report pain and putting them at greater risk for poor assessment and ineffective management of pain. However, the change in pain processing during later life is more complex (Monroe, Carter, Feldt, Tolley, & Cowan, 2012), as showed in another study (Horgas, Nichols, Schapson, & Vietes, 2007) that older adults become less able to endure strong pain sensations. Age-related physical/sensory changes in the CNS also explain reduced pain tolerance in the older adults (Hadjistavropoulos et al, 2014).…”
Section: Physical Painmentioning
confidence: 94%
“…McDonagh et al (2016) suggested that age-related changes in the processing and interpretation of pain may imped the sensation of pain among older adults, thereby reducing their ability to self-report pain and putting them at greater risk for poor assessment and ineffective management of pain. However, the change in pain processing during later life is more complex (Monroe, Carter, Feldt, Tolley, & Cowan, 2012), as showed in another study (Horgas, Nichols, Schapson, & Vietes, 2007) that older adults become less able to endure strong pain sensations. Age-related physical/sensory changes in the CNS also explain reduced pain tolerance in the older adults (Hadjistavropoulos et al, 2014).…”
Section: Physical Painmentioning
confidence: 94%
“…Eight studies were conducted in Europe [17,18,19,20,21,22,23,24,25] and two studies in the USA [26,27]. Five studies examined outcomes in nursing homes [23,24,25,26,27], whereas five studies examined outcomes in community-dwelling people or patients recruited from outpatient clinics [17,18,20,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The mean subject age ranged from 70 to 86 years. Three studies focused solely on people with AD [17,21,22,27], five studies included people with AD, VaD, mixed pathologies and/or DLB [20,23,24,25,26], one study was a case-control study of AD and DLB [18] and one study included dementia subtypes based on motor neuron symptoms (i.e. parkinsonian syndromes) [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations